Strategi Pengembangan LKMS-BMT Maslahah Sidogiri Pasuruan (Studi Analisis Pendekatan Interpretatif Struktural Modeling) (Strategy of LKMS-BMT Development Maslahah Sidogiri Pasuruan (Analysis Study of Structural Modeling Interpretative Approach)) - Parmujianto Parmujianto (Perisai : Islamic Banking and Finance Journal, 2020)
BMT (BMTM) is one of the LKMS that provides Sharia-based financial services. BMTM has not made specific identifications related to the behavior of the target audience which could potentially be a challenge in the future. This study uses a qualitative approach, namely descriptive analysis and Interpretative Structural Modeling (ISM). The results showed that consumer behavior in BMTM is positive in the utilization of BMTM products. Understanding and positive attitude towards BMTM products is based on the motives of daily necessities and business development. The efforts of BMT in building consumer loyalty to BMT by bringing services closer to the community, increasing the ratio of supervisors and discipline of supervision and developing several products according to community needs, as well as strengthening human resources.